2017
DOI: 10.1080/23744235.2017.1353704
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of immune responses to vaccine against haemorrhagic fever with renal syndrome in healthy adults aged 16–60 years: results from an open-label2-year follow-up study

Abstract: The two primary doses could help healthy individuals to generate an immune response, and this three-dose series may be better than a two-dose regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The Epidemiology of HFRS and HCPS China has the highest incidence and mortality of HFRS in the world, accounting for more than 90% of the total number of HFRS cases in the world (Zheng et al, 2018). In 2004, the Chinese Center for Disease Control and Prevention (China CDC) established the National Notifiable Disease Surveillance System (NNDSS) online, and HFRS cases of the whole country were reported daily through this system (Zhang et al, 2014).…”
Section: The Re-emergence Of Hantavirusmentioning
confidence: 99%
See 2 more Smart Citations
“…The Epidemiology of HFRS and HCPS China has the highest incidence and mortality of HFRS in the world, accounting for more than 90% of the total number of HFRS cases in the world (Zheng et al, 2018). In 2004, the Chinese Center for Disease Control and Prevention (China CDC) established the National Notifiable Disease Surveillance System (NNDSS) online, and HFRS cases of the whole country were reported daily through this system (Zhang et al, 2014).…”
Section: The Re-emergence Of Hantavirusmentioning
confidence: 99%
“…We can observe that the annual average number of cases in Shaanxi Province was higher than 2000, ranking at the top of the list (Figure 1). From 2006 to 2017, Shaanxi has gradually become the province with the highest incidence in China, with approximately 4.51 cases/100,000 cases, of which more than 90% are concentrated in the central region (Xi'an, Xianyang, Baoji, and Weinan cities) (Zheng et al, 2018). By November 20 of 2017, 878 people were recorded infected in Shaanxi Province (Dong et al, 2019).…”
Section: The Re-emergence Of Hantavirusmentioning
confidence: 99%
See 1 more Smart Citation
“…A second attenuated tetravalent Dengue vaccine is under development by Takeda and has shown promising results in a phase 2 clinical trial [23]. There are now two licensed inactivated hantavirus vaccines which are available in South Korea (Hantavax), and China (HFRS vaccine) [24][25][26], but these vaccines are not available elsewhere. Inactivated plague vaccines have been manufactured since the 1890s [27] however there are currently no vaccines of this type being marketed.…”
Section: Progress Towards Disease Controlmentioning
confidence: 99%
“…It combines Spatial Autocorrelation (SAR), a Spatial Moving Average (SMA) and Spatial Regression (SR). A large number of studies had shown that, whilst the ARIMA model provided better fitting results for data with a relatively stable temporal distribution and no strong spatial autocorrelation, its effectiveness for prediction relating to spatiotemporally heterogenous sample data was much weaker [ 30 32 ]. Cliff and Ord’s Spatiotemporal Autoregressive Integrated Moving Average (STARIMA) extended beyond the ARIMA model [ 33 ].…”
Section: Introductionmentioning
confidence: 99%